Multidimensional Poverty Index 2010 : two page briefing - Oxford Poverty & Human Development Initiative (OPHI) (Oxford Poverty & Human Development Initiative (OPHI), 2010)
The Multidimensional Poverty Index (MPI) is a new international measure of poverty. Covering 104 developing countries, the MPI complements income poverty measures by reflecting the acute deprivations that people face at the same time. It identifies people who context with multiple deprivations that people face at the same time. It identifies people who contend with multiple deprivations across three dimensions: education, health and living standards. The MPI was developed by the Oxford Poverty and Human Development Initiative (OPHI) and the United Nations Development Programme Human Development Report (UNDP HDR) to develop ideas and policies that can improve people’s lives.